The Influence of Annealing Temperature on Microstructure, Mechanical Properties, and Corrosion Resistance of Al-6Mg-0.4Mn-0.14Sc-0.12Zr Alloy Cold Rolling Plate - Lu, Liying; Jiang, Feng; Liu, Jiachen; Zhang, Jianjun; Wang, Guojun; Feng, Bo; Tong, Mengmeng; Tang, Zhongqin (Frontiers in Materials, 2020)
Al-6Mg-0.4Mn-0.14Sc-0.12Zr alloy with low Sc content was developed. The mechanical properties and corrosion resistance of Al-6Mg-0.4Mn-0.14Sc-0.12Zr alloy cold rolling plate annealed at different temperatures were studied and discussed. Based on OM, SEM, EDS and TEM techniques, the influence of annealing temperature on the microstructure of the alloy was studied. Besides, Sc-free alloy was also developed as the control group. The comparison between Sc-containing alloy and the control group was done of the mechanical properties and the microstructural characteristics for different processing conditions. In conclusion, when increasing annealing temperature, the corrosion resistance decreases first, and then increases. When annealed at 200℃ for 2 h, Al3Mg2 phase is precipitated continuously along the grain boundary, leading to a lowest corrosion resistance. When annealed at 350℃ for 2 h, the Al3Mg2 phase is not observed along the grain boundary, leading to a relatively high corrosion resistance. Moreover, the effective pinning of the grain boundaries by Al3(Sc,Zr) particles constrains the recrystallization. As a result, a preferable combination performance of the Sc-containing alloy cold rolling plate can be obtained with the tensile strength of 437 MPa, the yield strength of 318 MPa, the elongation of 14.8% and the corrosion resistance of 0.029 mm·a-1, respectively. The research findings provide theoretical and experimental supports on the industrial production of Al-Mg-Mn-Sc-Zr alloy with low Sc content.